Hydrogenation of Imines Catalyzed by 2‐(Aminomethyl)pyridine‐Based Ruthenium and Osmium Complexes. Issue 10 (15th July 2016) - Solinas, Maurizio; Sechi, Barbara; Baldino, Salvatore; Baratta, Walter; Chelucci, Giorgio
Abstract: CNN pincer ruthenium(II) and osmium(II) complexes of general formula RuCl(CNN)(dppb) (1 a ‐c ) and OsCl(CNN)(dppb) (2 a, b ) (dppb=Ph2 P(CH2 )4 PPh2, HCNN=[6‐( p ‐tolyl)‐2‐pyridyl]methylamine (4 ), N ‐methyl‐[6‐( p ‐tolyl)‐2‐pyridyl]methylamine (7 ) and N, N ‐dimethyl‐[6‐( p ‐tolyl)‐2‐pyridyl]methylamine (8 )) were prepared and assessed as catalysts in the hydrogenation of a variety of imines. Among the examined complexes, the Ru‐complex1 a, RuCl(4 )(dppb), showed the best activity, reducing N ‐aryl and N ‐alkyl imines to the related amines in high yields (up to 100 %) with a catalyst loading of 0.1‐1 mol% and under mild conditions (5 atm H2, 40‐70 °C). The Os‐complexes exhibited a lower activity than their ruthenium analogues. Despite this, the Os‐complex2 a, OsCl(4 )(dppb), was successful in the reduction of N ‐benzylideneaniline at 70 °C, affording a rare example of application of osmium complexes in the catalytic hydrogenation of imines. Abstract : The pincer complexes RuCl(CNN)(dppb) and OsCl(CNN)(dppb) (HCNN=[6‐( p ‐tolyl)‐2‐pyridyl]methylamine, N ‐methyl‐[6‐( p ‐tolyl)‐2‐pyridyl]methylamine and N, N ‐dimethyl‐[6‐( p ‐tolyl)‐2‐pyridyl]methylamine) were prepared and assessed as catalysts in the hydrogenation of a variety of imines. N ‐aryl and N ‐alkyl imines were reduced to the related amines in high yields (up to 100 %) with a catalyst loading of 0.1‐1 mol%, under mild conditions (40‐70 °C, 5 atm H2 ).